2024
DOI: 10.3390/ijms25020864
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Human Glucocorticoid Receptors in Fear Learning: A Multiscale Integrated Approach to Study Functional Connectivity

Simone Battaglia,
Chiara Di Fazio,
Matteo Mazzà
et al.

Abstract: Fear extinction is a phenomenon that involves a gradual reduction in conditioned fear responses through repeated exposure to fear-inducing cues. Functional brain connectivity assessments, such as functional magnetic resonance imaging (fMRI), provide valuable insights into how brain regions communicate during these processes. Stress, a ubiquitous aspect of life, influences fear learning and extinction by changing the activity of the amygdala, prefrontal cortex, and hippocampus, leading to enhanced fear response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 209 publications
0
18
0
Order By: Relevance
“…Studies using fMRI have consistently implicated the amygdala in the processing of fear-related stimuli during fear conditioning tasks. Increased amygdala activity is observed when participants Cellular Processes and Synaptic Interactions in Nuclei of the Amygdala DOI: http://dx.doi.org/10.5772/intechopen.1005123 are exposed to conditioned stimuli associated with fear, providing evidence for its involvement in fear learning and expression [77][78][79][80]. Beyond its role as a primary hub for fear processing, the amygdala interacts with other brain regions to modulate fear responses.…”
Section: Fear Conditioning Functional Imaging and Theta Rhythmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using fMRI have consistently implicated the amygdala in the processing of fear-related stimuli during fear conditioning tasks. Increased amygdala activity is observed when participants Cellular Processes and Synaptic Interactions in Nuclei of the Amygdala DOI: http://dx.doi.org/10.5772/intechopen.1005123 are exposed to conditioned stimuli associated with fear, providing evidence for its involvement in fear learning and expression [77][78][79][80]. Beyond its role as a primary hub for fear processing, the amygdala interacts with other brain regions to modulate fear responses.…”
Section: Fear Conditioning Functional Imaging and Theta Rhythmsmentioning
confidence: 99%
“…fMRI studies have revealed functional connectivity between the amygdala and various cortical and subcortical regions involved in emotional regulation, attention, and memory. These network interactions contribute to the complex processing of fear-related information and the regulation of emotional responses [77][78][79][80].…”
Section: Fear Conditioning Functional Imaging and Theta Rhythmsmentioning
confidence: 99%
“…For example, by downregulating phospho-ERK in pancreatic cancer cells, resveratrol inhibits the MAPK signaling pathway and nicotine’s potential to stimulate cell growth; meanwhile, kaempferol is able to inhibit the activity of MMP-9, by deactivating the MAPK/AP-1 pathway in breast cancer cells [ 72 ]. It has also been reported how polyphenols can interact with neural receptors and signaling pathways, for example the PI3K/Akt and ERK1/2 pathways, thereby influencing cellular responses [ 73 , 74 , 75 , 76 ]. Specifically, by modulating different cellular functions, polyphenols play an important role in neuroprotection being antioxidant, anti-inflammatory and anti-apoptotic.…”
Section: Polyphenolsmentioning
confidence: 99%
“…These functions are carried out by activating pathways such as the PI3K/Akt, Akt-ERK1/2 and MAPK [ 77 ]. Moreover, polyphenols have also been found to interact with neural substrates involved in the modulation of cytoskeletal dynamics [ 73 , 74 , 75 , 76 ].…”
Section: Polyphenolsmentioning
confidence: 99%
“…The complex interactions between cognitive and affective processes and their underlying neurobiological underpinnings have been the focus of much research. 22 , 23 Previous studies have shown that pituitary adenylate cyclase-activating polypeptides and vasoactive intestinal peptides play important roles in both metabolic and neurological diseases, so this may be the neural mechanism of the higher prevalence of hyperuricemia in psychiatric patients. 24 In clinical work, it has been noted that the probability of detecting HUA in patients with psychiatric disorders is high.…”
Section: Introductionmentioning
confidence: 99%